Fa'aliyyah Mawad Ta'lim Maharah al-Qira'ah li Tarqiyah Maharah al-Qira'ah al-Thullabah - Ubay, Ubay; Syaifullah, Muhammad; Murtadho, Nurul; Syuhadak, Syuhadak; Putri, Wakhidati Nurrohmah; Unsi, Baiq Tuhfatul (Institut Agama Islam Negeri Curup, 2023)
The purpose of this research was to determine the effectiveness of using teaching materials of reading to improve students’ reading skills at the Institute for Islamic Studies Ma’arif Nahdlatul Ulama (IAIMNU) in Metro Lampung. This research used the comparative quantitative method. For data analysis, the researchers used descriptive statistical analysis to produce the effectiveness of teaching materials for reading skills with a criterion based on descriptive perception in the degree to test the responses in the questionnaire scale. T-test using SPSS with Paired Sample Test was used to find out the differences between the results of before and after the experiment. Based on the statistical analysis, the value of experimental learning model was 14.462.The result of significance was Sig. (2-tailed) 000. The pre-test of academic achievement in reading - the post-test of academic achievement of reading was 8.295. The result of significance was Sig. (2-tailed) 000.The result of this research indicated that Hₒ was not acceptable, and H1was acceptable. The difference in the academic achievement of reading between before and after the experiment was indicative. Hence, the improvement of reading ability occurred after using reading materials designed based on David A. Kolb's experiential learning model.